Assessment of Agricultural Practices in Maize Crops (Zea mays) Based on Elemental Profile and Chemometrics Analysis - Zaldarriaga Heredia, Jorgelina (2019)
In this work the effects produced by two treatments onmaize crop samples have been studied. Analysis of maize grain based on twotypes of agronomical conditions was performed on: (a) lots treated withdifferent fertilizers and (b) lots with different crop density. Analysis wascarried out by microwave induced plasma with optical emission spectrometry (MIPOES) and included the quantification of 11 elements: Ca, Cd, Cr, Cu, Fe, Mg,Mn, Ni, P, Pb and Zn. With the purpose of understand the effect of agriculturalpractices on elemental profile, principal components analysis (PCA) and clusteranalysis (CA) were used as chemometrics tools, finding a correct grouping ofeach crop based on the type of treatment. The obtained models can be useful toevaluate agricultural strategies, as well as for determining potential yieldsin maize crops.